The level of environmental awareness among students to fulfill the aspiration of National Philosophy of Education. - Hassan, Aminuddin; Juahir, Hafizan; Jamaludin, Nur Syuhada (EuroJournals Publishing, 2009)
The major purpose of this paper is to investigate the philosophy of environmental education in Malaysian school system. The major contribution of this paper would be to help the respective agencies in the government in building up the environmental awareness among people starting from schools. It is part of the National Philosophy of Education to state the importance of this aspect. This paper embarks on the following objectives and expectations: (1) to identify the philosophy of environmental education in Malaysian school system from the perspective of the school management; (2) to determine the characteristics among schools members that are likely to influence the environmental awareness, (3) to determine the effectiveness of school-based environmental awareness programmes in order to enhance self-regulated strategies to school members; (4) to discover school members' attitudes towards the extensive environmental awareness programmes introduced by the respective authorities; and (5) to develop an environmental awareness suggestions. All these approaches will assist us in analyzing how far they impact on ‘the betterment of the personal well-being, family, society and the nation, as stated in the National Philosophy of Education by referring to the importance of having environmental awareness.